National Identity Construction in Cultural and Creative Tourism: The Double Mediators of Implicit Cultural Memory and Explicit Cultural Learning - Zhang, Shu-Ning; Ruan, Wen-Qi; Yang, Ting-Ting (SAGE open, 2021)
In light of the gap in the national identity research, this study proposes, constructs, and examines the path to national identity by using a mixed-method approach. Study 1 collected 502 questionnaires from Chinese tourists, and Study 2 conducted semi-structured interviews with 15 tourists. The findings confirm that cultural and creative tourism contributes to the construction of tourists’ national identity. Tourists’ long-term implicit cultural memory and short-term explicit cultural learning are the double guarantees for forming tourists’ cultural identity. Importantly, tourists’ cultural identity plays a critical mediating role in promoting national identity. Moreover, the interactive effect of cultural experience and creative performance accelerates the construction process of tourists’ national identity. This study consolidates the sociopolitical significance of cultural and creative tourism for national identity through a rare mixed method and identifies the specific role of the cultural factors affecting national identity, thereby providing great theoretical contributions and practical value.